2022
DOI: 10.3390/electronics11152285
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Approximation Methods for Trigonometric and Arctangent Calculations for Low-Performance Computers

Abstract: In modern computers, complicated signal processing is highly optimized with the use of compilers and high-speed processing using floating-point units (FPUs); therefore, programmers have little opportunity to care about each process. However, a highly accurate approximation can be processed in a small number of computation cycles, which may be useful when embedded in a field-programmable gate array (FPGA) or micro controller unit (MCU), or when performing many large-scale operations on a graphics processing uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Therefore, this nonlinear function is processed by approximation to achieve high speeds. The residual correction method proposed in our previous study [ 7 , 8 ] allowed calculations using only square root operations, as shown in the following equation. When , the maximum approximation error was less than 0.5 deg as showin in Figure 6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this nonlinear function is processed by approximation to achieve high speeds. The residual correction method proposed in our previous study [ 7 , 8 ] allowed calculations using only square root operations, as shown in the following equation. When , the maximum approximation error was less than 0.5 deg as showin in Figure 6 .…”
Section: Methodsmentioning
confidence: 99%
“…In human body motion measurement, and the posture measurement of robots and UAVs, real-time performance is required; thus, a high processing speed is vital. For this reason, we have been developing a fast approximate computation method for nonlinear functions as a fast attitude computation algorithm that can be used in embedded systems [ 7 , 8 ], and have used it in the above-mentioned wearable sensors and powered suits. This has enabled posture measurement on MCUs with small internal memory, where conventional mathematical libraries cannot be incorporated.…”
Section: Introductionmentioning
confidence: 99%
“…1(b). The thickness at different locations of the lens can then be obtained by relating the phase map of each single vortex beam ϕ 1,2 (x, y) as follows: 41,42 h = hmax[sin (ϕ 1 (x, y)) + sin (ϕ 2 (x, y))],…”
Section: Numerical Analysis a Acoustic Lens Designmentioning
confidence: 99%
“…Azim [7] presents a more modern approach wherein one can also do the approximation without technology. Kusaka [8] seeks to increase computation speeds for low performing computers, while Kumar [9] does the same thing for faster computers.…”
Section: Other Approaches Approximating the Trigonometric Functionsmentioning
confidence: 99%